Book Reviews. Issue 1 (1st April 2018) - Bellotta, Samanta; Negro, Francesca
Continental Shifts: Migration, Representation, and the Struggle for Justice in Latin(o) America, John D. 'Rio' Riofrio (2015)Austin, TX: University of Texas Press, 198 pp., ISBN: 9781477305423, h/bk, £20.99Sounds of Latinidad: Immigrants Making Music and Creating Culture in a Southern City, Samuel K. Byrd (2015)New York: New York UP, 304 pp., ISBN: 9781479859405, h/bk, £51.16, ISBN: 9781479860425, p/bk